PERAN BIPA SEBAGAI MEDIA PROMOSI DAERAH (KEK MANDALIKA) - Putra, Agus Darma; Wahidah, Baiq Yulia Kurnia (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Indonesian for Foreign Speakers (BIPA) plays a very active role as a regional promotional media. In this research, BIPA plays an active role as a regional promotional media, especially in the Mandalika Special Economic Zone (KEK). In this case, Mandalika utilizes natural resources and the cultural diversity of the local community as a tourist attraction that is introduced to foreign speakers. With the active role of BIPA, Mandalika has become a very popular tourist destination both locally, nationally and internationally. The aim of this research is to describe the role of BIPA as a regional promotional media in the Mandalika Special Economic Zone (KEK). Meanwhile, the method used in this research is a descriptive method with a qualitative approach. The results of this research are: (1) BIPA as a tourism promotion media in the Mandalika Special Economic Zone; (2) BIPA as a media for promoting religious culture; (3) BIPA as a media for promoting the art of Gendang Belek; (4) BIPA as a promotional media for the Bau Nyale tradition; and (5) BIPA as a media for promoting regional languages (Bahasa Sasak), and BIPA as a media for diplomacy.